2017
DOI: 10.1177/0255761416689841
|View full text |Cite
|
Sign up to set email alerts
|

Inside the fences: Pedagogical practices and purposes of songwriting in an adult male U.S. state prison

Abstract: We examined pedagogical strategies for facilitating and developing songwriting skills with 17 males incarcerated at a U.S. medium security prison. We also investigated the participants’ sense of self-worth, purpose, and social adjustment related to their participation in the songwriters’ workshops. The songwriting sessions spanned over two 13-week, 60-minute workshops and one nine-week 90-minute workshop, totaling 35 weeks. Using grounded theory procedures, we analyzed four types of data: 42 sets of original l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…11 In a study of 17 incarcerated males who underwent a 32-week collaborative songwriting intervention (CSI), participants were found to have improved adjustment to their incarceration along with increased personal skills. 12 The authors found the intervention facilitated trustworthy interactions among the incarcerated and helped to improve planning, pro-social, interpersonal, and emotional intelligence skills. 12 To date, research has not been conducted to assess the therapeutic effects of collaborative songwriting for veterans diagnosed with PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…11 In a study of 17 incarcerated males who underwent a 32-week collaborative songwriting intervention (CSI), participants were found to have improved adjustment to their incarceration along with increased personal skills. 12 The authors found the intervention facilitated trustworthy interactions among the incarcerated and helped to improve planning, pro-social, interpersonal, and emotional intelligence skills. 12 To date, research has not been conducted to assess the therapeutic effects of collaborative songwriting for veterans diagnosed with PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…(p. 47) Research suggests that songwriting is an all-consuming activity that could contribute to the participants' sense of personal expression (Anderson, 2012;Jurgensmeier, 2012;Morin, 2008;Stephenson, 2001;Tobias, 2010;Viega, 2013). Songwriting usually demands intense engagement and involvement of the participants, and a sense of being consumed with the activity at hand often gives participants a feeling of fulfillment as they engage in the songwriting process (Citron, 2008;Cohen & Wilson, 2012;Sena-Martinez, 2012;Tobias, 2010). These findings point toward Waterman's theory of psychological individualism.…”
Section: Overview Of the Conceptual Frameworkmentioning
confidence: 99%
“…Research cited above suggests that choral singing provides both a social and emotional outlet for participants who are incarcerated. The Songwriters' Workshop studied for this research organically evolved out of the prison choir, in which participants enjoyed the expression of emotion that they have experienced through making music together (Cohen & Hickey, 2012;Cohen & Wilson, 2012). In this instance, participants wanted to deepen their experience and express their original thoughts by writing their own music.…”
Section: General Music Programsmentioning
confidence: 99%
See 2 more Smart Citations